Effects of Syringic Acid on Apoptosis, Inflammation, and AKT/mTOR Signaling Pathway in Gastric Cancer Cells - Pei, Jinjin; Velu, Periyannan; Zareian, Mohsen; Feng, Zili; Vijayalakshmi, Annamalai (Frontiers in Nutrition, 2021)
Gastric cancer is one of the most common cancer and deadly disease worldwide. Despite substantial advances made in the treatment of gastric cancer, existing therapies still encounter bottlenecks. Chemotherapy, for instance, could lead to serious side effects, high drug resistance and treatment failure. Phytochemical-derived compounds from plants offer novel strategies as potent drug molecules in cancer therapy. Given the low toxicity and higher tolerance rate of naturally occurring compounds, the present study evaluated the effects of syringic acid on cytotoxicity, oxidative stress, mitochondrial membrane potential, apoptosis, and inflammatory responses in gastric cancer cell line (AGS). AGS cells were treated with various concentrations (5 - 40 μg/mL) of syringic acid for 24 h, after which cytotoxicity was analyzed. Reactive Oxygen Species (ROS), antioxidant enzyme activities, mitochondrial membrane potential (MMP, Δψm), cell morphologies, the expression of apoptotic markers and protein expression patterns were also investigated. Results indicated that syringic acid-treated cells developed anti-cancer activities by losing MMP, cell viability, and enhancing intracellular ROS. Syringic acid selectively developed apoptosis in a dose-dependent manner via enhanced regulation of caspase-3, caspase-9 and Poly ADP-ribose Polymerase (PARP) whereas decreasing the expression levels of p53 and BCL-2. Syringic acid also lowered activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) whereas Thio Barbituric Acid Reactive Substances (TBARS) increased. Syringic acid suppressed gastric cancer cell proliferation, inflammation, and induced apoptosis by upregulating mTOR via AKT signalling pathway. The study suggests syringic acid may constitute a promising chemotherapeutic candidate for gastric cancer treatment. Our study is the first report on the anti-cancer effects of syringic acid against gastric cancer cells via apoptosis, inhibition of inflammation, and the suppression of the mTOR/AKT signalling pathway.